Gliadin Nanoparticles Containing Doxorubicin Hydrochloride: Characterization and Cytotoxicity - Silvia Voci; Agnese Gagliardi; Nicola Ambrosio; Maria Cristina Salvatici; Massimo Fresta; Donato Cosco (MDPI AG, 2023)
Doxorubicin hydrochloride (DOX) is a well-known antitumor drug used as first line treatment for many types of malignancies. Despite its clinical relevance, the administration of the compound is negatively affected by dose-dependent off-target toxicity phenomena. Nanotechnology has helped to overcome these important limitations by improving the therapeutic index of the bioactive and promoting the translation of novel nanomedicines into clinical practice. Herein, nanoparticles made up of wheat gliadin and stabilized by polyoxyethylene (2) oleyl ether were investigated for the first time as carriers of DOX. The encapsulation of the compound did not significantly affect the physico-chemical features of the gliadin nanoparticles (GNPs), which evidenced a mean diameter of ~180 nm, a polydispersity index < 0.2 and a negative surface charge. The nanosystems demonstrated great stability regarding temperature (25-50 °C) and were able to retain high amounts of drug, allowing its prolonged and sustained release for up to a week. In vitro viability assay performed against breast cancer cells demonstrated that the nanoencapsulation of DOX modulated the cytotoxicity of the bioactive as a function of the incubation time with respect to the free form of the drug. The results demonstrate the potential use of GNPs as carriers of hydrophilic antitumor compounds.